Dendritic cells enhance the antigen sensitivity of T cells - Kreutzberg, Thomas; Garbi, Natalio (Frontiers in Immunology, 2012)
Naive T cells continuously migrate between the circulatory system and lymphoid organs, where they make dynamic contacts with rare dendritic cells (DCs) that strategically form an extensive dendrite network. In such a scenario, T cells spend most of their time quickly scanning the antigenic content of multiple DCs. These interactions provide the basis for efficient adaptive responses by increasing the probability of encounters between rare antigen-specific T cells and those DCs presenting the respective cognate antigens. In the absence of foreign antigen, however, T cells show different degrees of functional sensitivity towards TCR stimulation. Scanning of MHC/self-peptide complexes by naive T cells in the absence of infection is not without consequences but it increases their subsequent response towards antigenic challenge. This indicates that TCR sensitivity in naive T cells is tuned depending on the MHC/self-peptide signals they integrate from the environment even before T cells encounter cognate antigen. DCs have emerged as key components in providing MHC/self-peptide complexes and increasing the sensitivity of T cells towards subsequent TCR triggering. In the absence of cognate antigen, DCs maintain a tonic TCR signalling and license T cells for immune synapse maturation resulting in enhanced T cell responses towards a subsequent antigen stimulation. This review discusses recent findings on this subject and highlights the importance of the DC pool size for optimal T cell awareness to foreign antigen.